Efektifitas Home Program untuk Meningkatkan Kekuatan Otot Ekstremitas Bawah dan Resiko Jatuh Bagi Lanjut Usia di Posyandu Lanjut Usia Dusun Plosokerep, Bendosari, Sukoharjo - Komalasari, Dwi Rosella; Perdana, Suryo Saputra (Warta LPM, 2024)
Background: The incidence of falls in the elderly is increasing in the elderly population in worldwide and has been recorded decreasing the quality of life in the elderly. Exercise programs can increase lower extremity muscle strength, improve postural balance and reduce falling risk. Objective: to determine the effectiveness of the home program in increasing lower extremity muscle strength and reducing falling risk among the elderly in Plosokerep Village, Bendosari, Sukoharjo. Methods: Used counselling and providing home programs for strengthening lower extremity muscles to the elderly in Plosokerep Village, Bendosari and evaluated those observed between 19 February to 19 March 2022. Results: The home program showed increasing lower extremity muscle strength effectively (p<0.001). The improvement of knowledge about the importance of lower extremity muscle strength was indicated by an increase of average of muscle strength assessed by 5XSTS. The average of lower extremity muscle strength increased from 15.08 seconds to 13.45 seconds. The number of elderly who had a high risk of falling decreased by 25%. Home program exercise of lower extremity muscle showed effective results in increasing lower extremity muscle strength (p<0.001) and decreasing falling risk. Conclusion: Home program exercise is effective to the elderly to improve muscle strength of lower extremity and diminish falls in the elderly.